Over a million students use our free study notes to help them with their homework
So to start this question, we must multiply out the bracket as follows:2 x (y+3) = 10(2 x y) + (2 x 3) = 102y + 6 = 10Now we take away 6 from both sides of the equation:2y + 6 = 10 (NOW TAKE AWAY 6)2y = 4...
a) y = x/2 - 1 b) y = -2x + 9
5 tins of soup have a total weight of 1750 grams.--> from this, we can calculate the total weight of 1 tin of soup, with 1750÷5 = 350 grams4 t...
We will begin by eliminating fractions in the equation. To do this, the equation will be multiplied by 4 and (x+2), as these are the denominators of the two fractions.Multiplying by 4 gives:x - (8x/...
It relates back to what we actually mean why we say dy/dx. Simply put, dy/dx means the rate of change of y with respect to the rate of change in x over a infinitely small space of time. Therefore, when we...
←
623
624
625
626
627
→
Internet Safety
Payment Security
Cyber
Essentials